Global child poverty and well-being : measurement, concepts, policy and action - Minujin Z., Alberto; Nandy, Shailen (Bristol : Policy, 2012)
This book brings together theoretical, methodological and policy-relevant contributions by leading researchers on international child poverty.
Title from publisher's bibliographic system (viewed on 07 Sep 2022).
Keywords: Poor children; Poor children -- Research -- International cooperation; Poor children -- Services for -- International cooperation; Poverty